Pelatihan Penyusunan Perangkat Pembelajaran Pada Guru Mata Pelajaran Ilmu Pengetahuan Sosial Di Kabupaten Barru - Bustan Bustan; Supriadi Torro; Rusdi Rusdi (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2022)
This activity aims to provide training to subject IPS teachers in Barru district to increase understanding and skills in preparing plans to evaluating learning. The main target of the activity is the Student Subject Teacher Consultation (MGMP), Social Sciences (IPS) both teaching integrated social studies subjects and those which are still divided between History, Economics, Geography and Sociology subjects. The place of implementation of the activity is in the hall of the district education office. The results of the dedication show their seriousness and sincerity in following the training material. The material presented is curriculum review, Jigsaw learning models, making worksheets and learning reflections. The driving factor is the active participation of the participants while the inhibiting factor is the limited time and inadequate LCD facilities.